Downstreaming of Natural Resources in the Perspective of Islamic Jurisprudence (Fiqh): Weighing Its Maslahah and Mafsadah for the Ecosystem, Environment, and Humanity - Zumrotus Sholikatun Nurjanah; Ah. Soni Irawan; Yayan Musthofa (Al Wajiz: Journal of Sharia and Economics Studies, 2026)
Downstreaming of natural resources has become a strategic policy in many developing countries, including Indonesia, as an effort to increase commodity value through domestic processing and reduce dependence on raw material exports. However, downstreaming practices—particularly in the mining and plantation sectors—often present a dilemma between economic gains and environmental damage as well as social injustice. This research examines natural resource downstreaming from the perspective of environmental fiqh, grounded in sharia principles such as trusteeship over the earth, social justice, and ecosystem preservation, with a focus on weighing maslahah and mafsadah for the ecosystem, environment, and local communities. A qualitative approach based on literature study is employed, including analysis of downstreaming policies in Indonesia, empirical studies of environmental and social impacts, and fiqh literature related to the ethics of natural resource management. Data were collected from three main sources: classical and contemporary fiqh books related to hifẓ al-bī’ah (environmental preservation), government policy reports on natural resource downstreaming in Indonesia, and academic literature and international journals on natural resource management and environmental sustainability. The analysis was conducted using a descriptive-critical method, which allows the researcher to connect fiqh principles with downstreaming practices and to assess the maslahah and mafsadah for the community. The findings indicate that natural resource downstreaming has significant maslahah potential including increased economic added value, job creation, and regional welfare development. For example, the downstreaming policy for minerals such as nickel has contributed to national and regional income. However, if not balanced with environmental regulations and ethical implementation, downstreaming can cause mafsadah in the form of environmental degradation, deforestation, pollution, and inequality in benefit distribution. Therefore, this paper recommends the integration of environmental fiqh norms into natural resource downstreaming policies, including distributive justice, sustainable management, and participatory community oversight. With such an approach, natural resource downstreaming becomes not merely an economic strategy but a sustainable, just, and responsible development effort in order to preserve the maslahah of the people, the ecosystem, and the environment.